The Effect of Transformational and Transactional Leadership on Employee Negative Behavior Mediated by Work Stress - Valentina Happy Vanesa (Publisher Cv. Inara, 2021)
The objectives of this research was analyzed the effect of transactional leadership on work stress , the effect of transactional leadership on employee negative behavior, the effect transformational leadership on work stress, the effect of transformational leadership on employee negative behavior, and the effect of positively work stress on employee negative behavior. This research also analyzed the impact of transformational and transactional leadership on employee negative behaviour through work stress. The population of this study consist of two hundred employees PT. X Jakarta as the respondents provided the data that were analyzed for this study. Using the sub-set of the sampling consisting of was used to test five hypothesized relationship in the model. Data analysis in this research was used Structural Equation Model (SEM) to test independent variables influence the dependent variable. The result of this research conclude that there is positive impact from transactional leadership on work stress and negative impact from transformational leadership on work stress. The result of the study also revealed that theres in and positive indirect impact from transactional leadership on employee negative behaviour through work stress and negative indirect impact from transformational leadership on employee negative behaviour through work stress.